Inhibitory Effect of Rehmannia Glutinosa Pharmacopuncture Solution on β-hexosaminidase Release and Cytokine Production via FcεRI signaling in RBL-2H3 Cells - Kyung-Hwa Kang; Cheol-Hong Kim (Korean Pharmacopuncture Institute, 2011)
Background: Type I allergy is involved in allergic asthma, allergic rhinitis, and atopic dermatitis which are accompanied by an acute and chronic allergic inflammatory responses. Rehmannia glutinosa is a traditional medicine in the East Asian region. This study examined whether a Rehmannia Glutinosa pharmacopuncture solution (RGPS) had anti-allergic or anti-inflammatory effects in antigen-stimulated-RBL-2H3 cells. Methods: We determined the effect of RGPS on cell viability using the 3-[4,5-dimethylthiazolyl]-2,5-diphenyltetrazolium bromide (MTT) assay. We also examined the effect of RGPS on the release of β-hexosaminidase and the secretion of IL-4 and TNF-α using ELISA. In addition, we evaluated the effect of RGPS on the mRNA expression of various cytokines; IL-2, IL-3, IL-4, IL-5, IL-13 and TNF-α using RT-PCR. Furthermore, we assessed the activation of mitogen-activated protein kinases (MAPKs) and nuclear factor (NF)-κB using Western blotting after RGPS treatment. Results: We found that RGPS (10-4 to 10-1 dilution) did not cause any cytotoxicity. We observed significant inhibition of β-hexosaminidase release and suppression of the protein secretion of IL-4 and TNF-α and mRNA expression of multiple cytokines in antigen-stimulated-RBL-2H3 cells after RGPS treatment. Additionally, RGPS suppressed not only the phosphorylation of MAPKs, but also the transcriptional activation of NF-κB in antigen-stimulated-RBL-2H3 cells. Conclusions: These results suggest that RGPS inhibits degranulation and expression of cytokines including IL-4 and TNF-α via down-regulation of MAPKs and NF-κB activation in antigen-stimulated-RBL-2H3 cells. In conclusion, RGPS may have beneficial effects in the exerting anti-allergic or anti-inflammatory activities.